2006
DOI: 10.1016/j.stam.2006.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Chiroptical study and conformation analysis of helical polymers surrounded by helical hydrogen-bonding strands

Abstract: The chiroptical properties of poly((S)-N-(3-butynyl)-3-methylpentanamide) (poly(1)) were studied, and the conformation was analyzed. Poly(1) exhibited a large specific rotation and Cotton effect in CHCl 3 , indicating that it took a helical structure with predominantly one-handed screw sense. From liquid state IR spectroscopic analysis along with molecular mechanics and semiempirical molecular orbital calculations, it was concluded that the helix was stabilized by intramolecular hydrogen-bonding strands betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The addition of acetylacetone (acac) reversed the helicity, causing the recovery of the original CD spectra in all cases. [8] AFM also shows multistranded lefthanded helices, in which interchain hydrogen bonds are likely to play a main role [9] (Figure 2 b). The images show two types of structures ( Figure 2): individual and associated chains.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of acetylacetone (acac) reversed the helicity, causing the recovery of the original CD spectra in all cases. [8] AFM also shows multistranded lefthanded helices, in which interchain hydrogen bonds are likely to play a main role [9] (Figure 2 b). The images show two types of structures ( Figure 2): individual and associated chains.…”
mentioning
confidence: 99%
“…w1 % + 1488, Figure 2 c). [8] AFM also shows multistranded lefthanded helices, in which interchain hydrogen bonds are likely to play a main role [9] (Figure 2 b). [8] AFM also shows multistranded lefthanded helices, in which interchain hydrogen bonds are likely to play a main role [9] (Figure 2 b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, earlier computational studies 13,14 had found that overlapping adjacent monomers yield helical conformations. Also protein-like folds are adopted by a host of non-biological polymers 15,16,17,18,19,20,21 (see Appendix).…”
mentioning
confidence: 99%
“…In the former pattern, it forms between the amide groups at nth and (n + 2)th units, while in the latter one, it forms between the amide groups at nth and (n + 3)th units. The CD signals of these two types of helical patterns appear around 390 and 300 nm, respectively [38]. In the present study, the main chains of Poly(V 1-3 ) could be considered to form a tight helix according to the CD and UV spectra.…”
Section: Conformation Of Poly(v 1-3 ) In Solutionmentioning
confidence: 68%